Modelling and theoretical understanding of the isotope effect from JET experiments in view of reliable predictions for deuterium-tritium plasmas. (1st May 2022) - Garcia, J; Casson, F J; Bañón Navarro, A; Bonanomi, N; Citrin, J; King, D; Mantica, P; Mariani, A; Marin, M; Mazzi, S; Viezzer, E; ,
Abstract: This is an overview of the theoretical understanding of the so-called isotope effect in JET hydrogen versus deuterium plasmas. Experimentally, weak to moderate deviations from naive GyroBohm scaling expectations are found for the core heat transport in L and H-modes. The physical mechanisms behind such deviations are analysed in the framework of the gyrokinetic theory. In the case of particle transport, isotope effects are mostly found in the plasma edge where the density is higher in deuterium than in hydrogen plasmas. In general, both the thermal energy and particle confinement increase with increasing main ion mass. A comparison of such results to expectations for deuterium-tritium plasmas in ITER is discussed.